Association of Fetuin‐A With Incident Fractures in Community‐Dwelling Older Adults: The Cardiovascular Health Study. (21st May 2015) - Fink, Howard A; Bůžková, Petra; Garimella, Pranav S; Mukamal, Kenneth J; Cauley, Jane A; Kizer, Jorge R; Barzilay, Joshua I; Jalal, Diana I; Ix, Joachim H
Abstract Fetuin‐A, a serum protein that regulates calcium mineralization, has been associated with bone mineral density (BMD) in several cross‐sectional human studies, suggesting a possible beneficial effect on clinically important measures of bone health. Fetuin‐A and incidence of subsequent fracture was assessed in 4714 men and women ≥65 years of age. Proportional hazards models were used to estimate risk of incident hip (hospital discharge ICD‐9 codes) and composite fracture (hip, pelvis, humerus, or proximal forearm; hospital discharge ICD‐9 codes and Medicare claims data). A total of 576 participants had an incident hip fracture (median follow‐up 11.2 years) and 768 had an incident composite fracture (median follow‐up 6.9 years). In unadjusted analyses, there was no association between fetuin‐A (per SD increase) and risk of hip fracture (hazard ratio [HR], 0.96; 95% CI, 0.88 to 1.05) or composite fracture (HR, 0.99; 95% CI, 0.92 to 1.06). Results were not significantly changed after adjustment for potential confounding variables. Analyses modeling fetuin‐A in quartiles or within a subset with available BMD measures also showed no statistically significant association with risk of hip or composite fracture. Though fetuin‐A was positively associated with areal BMD in partially adjusted models (total hip: β, 0.013 g/cm2; 95% CI, 0.005 to 0.021; femoral neck: β, 0.011 g/cm2; 95% CI, 0.004 to 0.018; and lumbar spine: β, 0.007 g/cm2; 95% CI, 0.001 to 0.028), these associations were no longer significant after further adjustment for BMI and in final multivariate models. In this large sample of community‐dwelling older adults, a small positive association between fetuin‐A and areal BMD appeared attributable to confounding variables and we found no evidence of an association between fetuin‐A and risk of clinical fracture. © 2015 American Society for Bone and Mineral Research © 2015 American Society for Bone and Mineral Research.